Is utility transferable? a revealed preference analysis - Laurens Cherchye; Thomas Demuynck; Bram De Rock (Theoretical Economics, 2015)
The transferable utility hypothesis underlies important theoretical results in household economics. We provide a revealed preference framework for bringing this (theoretically appealing) hypothesis to observational data. We establish revealed preference conditions that must be satisfied for observed household consumption behavior to be consistent with transferable utility. We also show that these conditions are testable by means of integer programming methods.
Keywords: C14; D1; D11; D12; D13; 330; Transferable utility hypothesis; generalized quasi-linearity; household consump- tion; nonparametric tests; revealed preferences